Verses mentioned on condemn extremism at people of bible in termed and meaning objective study (Journal of the College of Basic Education, 2022)
This research concluded a very renewable, vital subject which is the importance of the youth’s role in facing all terrorism and extremism thoughts. Those bad thoughts were the main reason of society’s destruction in the past and present times. Therefore it is important to give youths vital role in facing these dangerous diseases, this vital role can be represented by some different sides we will explain some of them in this research in two chapters. The first chapter mention’s the concept of youths, terrorism and extremism and other related words, while the second chapter was about the role of youths in facing terrorism and extremism using science and presenting the mildness method and the Islamic eminence and easiness. These chapters were divided into three objectives; the first objective was about the youth facing role through teaching and studying, while; the second one was about the Islamic religion balances and mildness. And the last objective was about the easiness of Islam by the Extrapolation of the prophet speeches and their referring meanings in following the ancient method against the destructive thoughts.